Tantangan Orang Tua dalam Membimbing Anak Selama Belajar Daring - Ameliana Agustia Ningsih; Fatmariza Fatmariza; Azwar Ananda; Maria Montessori (Journal of Civic Education, 2023)
This study aims to address the challenges faced by parents and strategies to overcome the difficulties associated with online learning. The motivation for this research comes from the increasing number of parents encountering obstacles in guiding their children's education amidst the prevalence of online learning, particularly during the pandemic. Employing a qualitative approach, this study utilizes a case study method to investigate the difficulties encountered by parents and explore potential solutions. Informant selection is conducted through purposive sampling, involving both parents and teachers. Primary data is collected through various means such as observation, interviews, and documentation studies. To ensure data validity, triangulation is employed, and data analysis encompasses techniques such as data reduction, data presentation, and drawing conclusions. The research findings reveal that parents employ several strategies to mitigate online learning challenges, including accompanying and supervising their children, creating a conducive study environment, providing regular reminders for completing tasks, sourcing supplementary learning materials, maintaining communication with teachers, balancing household responsibilities with assisting children, and optimizing teaching opportunities. While this research primarily focuses on parents' perspectives, it acknowledges that children also face difficulties during online learning.